2009
DOI: 10.1111/j.1440-1819.2009.01925.x
|View full text |Cite
|
Sign up to set email alerts
|

Internet overuse and excessive daytime sleepiness in adolescents

Abstract: Aim:The purpose of this study was to examine the association of Internet overuse with excessive daytime sleepiness (EDS).Methods: A total of 2336 high school students in South Korea (boys, 57.5%; girls, 42.5%) completed the structured questionnaire. The severity of Internet addiction was evaluated using Young's Internet addiction test. Results:The proportions of boys who were classified as Internet addicts and possible Internet addicts were 2.5% and 53.7%, respectively. For girls, the corresponding proportions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
189
3
10

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 300 publications
(234 citation statements)
references
References 33 publications
21
189
3
10
Order By: Relevance
“…A total of seven studies used the IAT for Internet addiction assessment in adolescents and children aged 8 to 24 years [61][62][63][64][65][66][67], with sample sizes ranging from 1,618 [65] to 17,599 participants [63]. Although the same measurement instrument has been used in these studies, various cut-offs have been applied to demarcate addiction or excessive use across studies.…”
Section: Prevalence Of Internet Addiction In Adolescentsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of seven studies used the IAT for Internet addiction assessment in adolescents and children aged 8 to 24 years [61][62][63][64][65][66][67], with sample sizes ranging from 1,618 [65] to 17,599 participants [63]. Although the same measurement instrument has been used in these studies, various cut-offs have been applied to demarcate addiction or excessive use across studies.…”
Section: Prevalence Of Internet Addiction In Adolescentsmentioning
confidence: 99%
“…Comorbid symptoms have included alcohol and substance use [47,48,51,65,66,71,74,82,86], proneness for problem behaviours [82], depression [48,50,67,68,78,81,83,87,124], suicidal ideation [124][105], ADHD [67,79,157], social phobia and phobic anxiety [79,84,87], schizophrenia, obsessive-compulsive disorder [67], psychoticism [71], and antisocial/aggressive behaviours [48,72,79,80,87]. Finally, a number of psychosomatic problems have been linked to problematic Internet use, such as a poor health condition, excessive daytime sleepiness [66], lack of energy, physiological dysfunction, weakened immunity [63], obesity, and poor vision [49].…”
Section: Comorbid Symptomsmentioning
confidence: 99%
“…A study undertaken on Taiwanese college students identified sleep deprivation as an important negative consequence of excessive internet use 1 . Excessive daytime sleepiness was recorded as an important finding among internet addicts in a study undertaken on Korean adolescents 4 . These results significantly imply the dependence behaviour of internet addicts, who use the internet indiscriminately, at the expense of more important and purposeful activities of day to day life.…”
Section: Discussionmentioning
confidence: 99%
“…Also, this could have a negative impact on their lifestyle, with a gradual transformation to a more sedentary lifestyle. Some cross-sectional studies have shown that internet addiction has an adverse effect on several lifestyle-related factors in adolescents; it can result in irregular dietary habits, extended periods of time spent on the internet 2 , physical inactivity and short duration of sleep 3,4 . Also, with late night internet use, as is often the case with adolescents, the quantity and quality of sleep is significantly compromised.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation